Monitoramento de material particulado atmosférico no centro da cidade de João Pessoa-PB - Medeiros, Larissa Cavalcanti de Sousa (2020)
Air pollution, mainly from particulate matter, is becoming more and more worrying due to serious health problems. According to the World Health Organization, millions of people die every year from illnesses caused by air pollution. According to CONAMA Resolution 491/2018, environmental agencies in Brazilian municipalities must monitor air quality. In view of this need, this study aimed to monitor particulate material in the center of João Pessoa, which until then had not carried out air quality studies, in order to find out if the concentrations were within the resolution limits. Assess the relationship between concentrations and meteorological variables and monitor every 3 hours to observe how the concentration varies during the day. Samples of MP2.5, MP10 and MP PTS were taken with the HiVol 3000 equipment, within 10 days of sampling for each type of particulate material, using a glass fiber filter to retain the material. The equipment was installed in the SUDEMA - Environment Administration Superintendence building, located in the center of João Pessoa. The concentrations of particulate material were determined by the gravimetric method. CONAMA 491/2018 establishes that the concentrations of MP2.5 must not exceed the value of 60µg / m3 in Intermediate Period 1 (PI1) and 25µg / m3 in the Final Period, for MP10, in (PI1) is 120 µg / m3 and in the Final Period it is 50 µg / m3 and for PTS they cannot exceed 240 µg / m3 daily. The following concentrations were found: for MP2.5 (8.7013 ± 1.6969 µg / m3), for MP10 (20.8561 ± 3.0295 µg / m3) and for MP PTS (30.6057 ± 3.9618µg / m3). The concentrations found were below the limits established by Conama, characterizing a good quality in the air in that point of the city. To assess the correlations between particulate matter concentrations and meteorological variables, Pearson's correlation coefficients were calculated at a significance level of 5% (p≤0.05). The MP2.5 had a greater positive correlation with the temperature, the MP10 had a greater positive correlation with the wind speed and the PTS obtained a greater negative correlation with the temperature. Monitoring every 3 hours for a day showed that concentrations vary according to the flow of vehicles at certain times.